Computed tomographic colonography for colorectal cancer screening. Issue 14 (10th June 2013) - Hassan, Cesare; Pooler, B. Dustin; Kim, David H.; Rinaldi, Antonio; Repici, Alessandro; Pickhardt, Perry J.
<x xml:space="preserve">Abstract</x> BACKGROUND The objective of this study was to determine whether age, sex, a positive family history of colorectal cancer, and body mass index (BMI) are important predictors of advanced neoplasia in the setting of screening computed tomographic colonography (CTC). METHODS Consecutive patients who were referred for first‐time screening CTC from 2004 to 2011 at a single medical center were enrolled. Results at pathology were recorded for all patients who underwent polypectomy. Logistic regression was used to identify significant predictor variables for advanced neoplasia (any adenoma ≥10 mm or with villous component, high‐grade dysplasia, or adenocarcinoma). Odds ratios (ORs) were used to express associations between the study variables (age, sex, BMI, and a positive family history of colorectal cancer) and advanced neoplasia. RESULTS In total, 7620 patients underwent CTC screening. Of these, 276 patients (3.6%; 95% confidence interval [CI], 3.2%‐4.1%) ultimately were diagnosed with advanced neoplasia. At multivariate analysis, age (mean OR per 10‐year increase, 1.8; 95% CI, 1.6‐2.0) and being a man (OR, 1.7; 95% CI, 1.3‐2.2) were independent predictors of advanced neoplasia, whereas BMI and a positive family history of colorectal cancer were not. The number needed to screen to detect 1 case of advanced neoplasia varied from 51 among women aged ≤55 years to 10 among men aged >65 years. The number of post‐CTC colonoscopies needed to detect 1 case of advanced neoplasia varied from 2 to 4. CONCLUSIONS Age and sex were identified as important independent predictors of advanced neoplasia risk in individuals undergoing screening CTC, whereas BMI and a positive family history of colorectal cancer were not. These results have implications for appropriate patient selection. Cancer 2013;119:2549–2554. © 2013 American Cancer Society.